Taxonomy of South American species of Ceratina (Calloceratina) Cockerell, 1924 with comments on new species-groups proposed for this subgenus (Hymenoptera: Apidae: Xylocopinae) - Mahlmann, Thiago; Oliveira, Favízia Freitas de; Oliveira, Marcio Luiz de (EntomoBrasilis, 2023)
Two new species of the small carpenter bee genus Ceratina (Calloceratina) Cockerell, 1924 are described and illustrated. Ceratina (Calloceratina) mourei new species, and Ceratina (Calloceratina) silveirai new species, form the silveirai species-group, a very distinct set within the subgenus C. (Calloceratina). The taxonomy of South American species was approached, being redescribed and illustrated the species Ceratina (Calloceratina) chloris (Fabricius, 1804) and Ceratina (Calloceratina) triangulifera Cockerell, 1914, proposing the chloris species-group for them. The diagnosis for the subgenus Calloceratina is presented and an identification key for the South American species is also proposed.